Discovering the Influence of Identity, Moral Development, and Supportive Relationships on Mental Health and Academic Success in Adolescence - Maspul, Kurniawan Arif (EDUJAVARE: International Journal of Educational Research, 2023)
Adolescence is a critical period characterized by profound transformations in identity, moral cognition, and relational dynamics. This qualitative research study employs a multifaceted approach, combining discussions, observations, and literature review, to gain a comprehensive understanding of the interconnected elements of adolescent development. Through in-depth discussions with adolescents, educators, and caregivers, as well as observations in diverse educational settings, this study captures the nuanced interplay and complexities of adolescent identity formation, moral growth, and the role of supportive relationships. Thematic analysis of the collected data reveals significant insights into the impact of these factors on mental health, psychosocial functioning, and academic motivation. By integrating findings with existing literature, this study contributes to the knowledge base, providing practical strategies and implications for educators, caregivers, and researchers to foster positive adolescent development, well-being, and academic success. Ultimately, this research aims to promote holistic support for adolescents during this pivotal developmental stage.